SIMULATION OF PHYSICAL PROCESSES BY METHOD ONE-DIMENSIONAL DIFFERENTIAL BORDER TRANSFORMATIONS TASKS - Baranov , V. L.; Vodopyan , S. V.; Kostyuchenko , R. M. (Problems of Informatization and Management, 2005)
A method for modeling physical processes based on one-dimensional differential transformations of boundary value problems is proposed. Examples of modeling are given.